Purple Sweet Potato Extract Effects On Tnf-Α And Gut Injury - Anak Agung Ayu Hellin Chandrakirana; Agus Roy R.H. Hamid; I Gusti Putu Hendra Sanjaya; I Gusti Ayu Sri Mahendra Dewi; Putu Anda Tusta Adiputra (Eduvest - Journal of Universal Studies, 2025)
The purpose of this study was to evaluate the effect of oral administration of purple sweet potato (Ipomoea batatas L.) extract on serum and tissue TNF-α levels in the gaster and duodenum, as well as on gastrointestinal damage in Wistar rats (Rattus norvegicus) with major burns. This experimental research used a Randomized Post-Test Only Control Group Design with Wistar rats as subjects, divided into a control group (P0) and a treatment group (P1). The results showed that serum TNF-α levels were significantly lower in the treatment group compared to the control group (p = 0.002). Tissue TNF-α levels also decreased significantly (p = 0.049), suggesting a local anti-inflammatory effect on the intestinal mucosa. Statistical analysis demonstrated that mucosal thickness was higher in the treatment group, with a mean difference of 270.32 µm (p < 0.001). However, there was no significant difference in villi width between groups (p = 0.129). Significant differences were observed in mucosal necrosis lesions (p < 0.001), hemorrhage lesions (p < 0.001), and inflammation lesions (p = 0.001) between the treatment and control groups. In conclusion, oral administration of purple sweet potato extract effectively reduced serum and tissue TNF-α levels, increased intestinal mucosal thickness, and protected against mucosal damage in rats with major burns. These findings indicate the potential of purple sweet potato extract as an adjuvant therapy to reduce systemic inflammation and improve intestinal mucosal integrity in burn conditions.